Woody Debris and Nutrient Retention following Alternative Biomass Harvesting Guidelines. Issue 2 (21st September 2018) - Kabrick, John M; Goyne, Keith W; Stelzer, Henry E
Abstract: Concern about excessive woody debris removals during biomass harvests has led to the development of biomass harvesting guidelines (BHGs) for retaining woody debris for habitat and nutrient cycling. However, the efficacy of BHGs has not been experimentally examined. Two BHG treatments applied during clearcutting and thinning operations were examined in a replicated complete-block experiment. The first BHG treatment included the retention of one-third of tops of trees ≥8 in. dbh and one-third of trees <8-in. dbh. The second included the retention of all tops of trees ≥8-in. dbh and no restriction on the removal of smaller trees. In clearcuts, the two BHGs each increased the biomass of woody debris retained by 1.7 times compared to where no BHG was applied. However, in thinned units, there were no differences in retained woody debris regardless of BHG application. Nutrient retention trends followed those of biomass. Nutrients retained in woody debris generally exceeded nutrient removals in harvested wood except for calcium, for which removals equaled retention where BHGs were applied and exceeded retention in the absence of BHGs. Findings suggest that applying BHGs for retaining woody debris becomes more important as harvest intensity increases.